Comparative Evaluation of Incision and Drainage Versus Percutaneous Aspiration in the Management of Breast Abscesses - Farwa Zohaib, Huma Aslam, Jawad Ahmed, Irshad Ahmad, Tanvir Ahmad Bhatti, Sabtain Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Breast abscesses are a common complication of lactational mastitis, often requiring interventional treatment. Objectives: To compare the clinical efficacy, patient outcomes, and complication rates of incision and drainage versus ultrasound-guided percutaneous aspiration in the treatment of breast abscesses. Methods: This prospective, comparative clinical study was conducted at Jinnah hospital Lahore during May 2022 to March 2023. A total of 86 female patients diagnosed with breast abscesses were enrolled based on predefined inclusion and exclusion criteria. All patients underwent baseline investigations including complete blood count, blood glucose, and breast ultrasound to determine the size, number, and location of abscesses. Microbiological cultures of aspirated pus or drained material were sent for analysis in both groups. Results: The mean resolution time was significantly shorter in the aspiration group (6.3 ± 2.1 days) compared to the I&D group (9.1 ± 2.7 days). Pain scores on Day 3 were lower in the aspiration group (VAS 3.2 ± 1.5 vs. 6.7 ± 1.2, p < 0.001). Breastfeeding continuation was significantly higher in the aspiration group (86.0% vs. 60.4%, p = 0.01), and cosmetic satisfaction was also superior. Although the recurrence rate was higher in the aspiration group (11.6% vs. 4.6%), the difference was not statistically significant (p = 0.23). Minor complications were comparable in both groups. Conclusions: It is concluded that ultrasound-guided percutaneous aspiration is an effective, minimally invasive alternative to incision and drainage in the treatment of breast abscesses, particularly in selected patients with uncomplicated, unilocular abscesses. It offers faster recovery, better cosmetic results, and greater support for continued breastfeeding. Keywords: Breast cancer, Patients, Women, Morbidity, health, Infection